PERAN SELF-EFFICACY DALAM MEMEDIASI PENGARUH PENGETAHUAN BERWIRAUSAHA, TINGKAT PENDIDIKAN, LINGKUNGAN KELUARGA, DAN PENGALAMAN KERJA TERHADAP MINAT BERWIRAUSAHA - Suci Atiningsih; Rudi Suryo Kristanto (STIE Pelita Nusantara Semarang, 2020)
The purpose of this study was to determine the role of self-efficacy in mediating the influence of entrepreneurial knowledge, education level, family environment, and work experience on interest in entrepreneurship.The research object was all SMEs players in the Banyudono sub-district, Boyolali district with a total sample size of 64 SMEs actors. The data analysis techniques used were multiple linear regression and sobel test. The results of this study are entrepreneurial knowledge, education level, and family environment have a positive and significant effect on self-efficacy, but work experience has no effect on self-efficacy. Entrepreneurial knowledge, education level, family environment and self-efficacy have a positive and significant effect on interest in entrepreneurship, but work experience has no effect on interest in entrepreneurship. Self-efficacy can mediate the influence of entrepreneurial knowledge, education level, family environment, and work experience on interest in entrepreneurship.The results of this study are expected to provide an empirical contribution to the role of self-efficacy in mediating the influence of entrepreneurial knowledge, education level, family environment, and work experience on interest in entrepreneurship